Mostar 2004: Workshop Four - Pašić, Amir, 1953-2022 (My University, 1998)
Fourth Workshop of Mostar 2004 Project organized by IRCICA and the City of Mostar between 20 and 31 July in 1998 in Mostar.
Brochure titled "Mostar 2004: IVth Workshop, Mostar, July 20-31, 1998".
File titled "Important Dates and Documents in Connection with Old Bridge Reconstruction" consists of photocopied documents.
Address of Dr. Hidayet Yavuz Nuhoğlu, Deputy Director General of the Research Centre for Islamic History, Art and Culture-IRCICA, at the opening of the fourth Workshop Mostar 2004.
Detailed information about the Mostar 2004 Project can be found in the following publication: Pašić, Amir (2005). Mostar 2004 Program 1994-2004: Final report. İstanbul: IRCICA. (IRCICA Library call. no. 720.949742 MO)
Keywords: Mostar-Bosnia and Herzegovina; Architecture-Bosnia and Herzegovina; Old Bridge-Mostar; Neziraga Mosque Complex-Mostar; Roznamedžijina Madrasah-Mostar; Cejvan Kethuda Hamam-Mostar